Sustainable Concrete Solutions: Advancing Low-Carbon Infrastructure with Fly Ash in Nigeria’s Construction Industry - Unegbu, Hyginus; Yawas, Danjuma S. (Journal of Sustainable Infrastructure, 2025)
The urgent environmental challenges posed by the high carbon footprint of ordinary Portland cement (OPC) demand sustainable alternatives in the construction industry. This study aims to evaluate the mechanical performance, durability, environmental impact, and economic feasibility of fly ash-based concrete as a partial replacement for OPC in Nigeria’s construction sector. Concrete mixtures with 20%, 40%, and 60% fly ash replacement were prepared and tested for compressive strength, workability, chloride penetration resistance, sulfate resistance, and water absorption. Advanced life cycle assessment (LCA) and economic analyses were conducted to quantify environmental benefits and cost savings. Results indicate that early-stage compressive strength decreases with increasing fly ash content due to slower pozzolanic reactions; however, significant strength gains occur at later curing stages, with 90-day compressive strengths reaching up to 42 MPa for 40% fly ash mixtures. Durability improvements were demonstrated by a 50% reduction in chloride permeability and a decrease in sulfate-induced mass loss from 0.7% to 0.2% at 60% fly ash replacement. The LCA revealed a reduction in CO₂ emissions by up to 51%, while economic analysis showed cost savings of up to 20% compared to conventional OPC concrete. These findings confirm that fly ash-based concrete provide enhanced durability and substantial environmental and financial advantages, making it a viable, sustainable alternative for construction in Nigeria. However, challenges such as supply chain constraints, quality control, and limited industry awareness must be addressed to enable widespread adoption. Future research should focus on improving fly ash reactivity, exploring hybrid supplementary cementitious materials, and conducting long-term field performance studies to further optimize and validate fly ash concrete applications under local climatic conditions.